PERAN GREEN ACCOUNTING, KINERJA LINGKUNGAN, CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KINERJA KEUANGAN PERUSAHAAN INDEKS SRI KEHATI - Diva Aulia Nurfitriani; Rudi Kurniawan; Herry Subagyo; Linda Ayu Oktoriza (MANAJEMEN, 2025)
Companies committed to sustainability are expected to improve their financial performance. However, the impact of Green Accounting, Environmental Performance, and Corporate Social Responsibility (CSR) on financial performance remains unclear, especially for companies listed in the SRI Kehati Index, which emphasizes sustainability principles, integrity in corporate management, and environmental awareness. This study examines the relationship between these three factors and financial performance using a quantitative approach with secondary data from nine companies. The analysis was conducted using panel data regression in EVIEWS 12. The results indicate that Green Accounting and Environmental Performance have no impact on financial performance, while CSR has a significant negative effect on financial performance.